Influence of sedation on delirium recognition in critically ill patients: A multinational cohort study. Issue 5 (September 2020) - van den Boogaard, Mark; Wassenaar, Annelies; van Haren, Frank M.P.; Slooter, Arjen J.C.; Jorens, Philippe G.; van der Jagt, Mathieu; Simons, Koen S.; Egerod, Ingrid; Burry, Lisa D.; Beishuizen, Albertus; Pickkers, Peter; Devlin, John W.
Abstract: Background: Guidelines advocate intensive care unit (ICU) patients be regularly assessed for delirium using either the Confusion Assessment Method for the ICU (CAM-ICU) or the Intensive Care Delirium Screening Checklist (ICDSC). Single-centre studies, primarily with the CAM-ICU, suggest level of sedation may influence delirium screening results. Objective: The objective of this study was to determine the association between level of sedation and delirium occurrence in critically ill patients assessed with either the CAM-ICU or the ICDSC. Methods: This was a secondary analysis of a multinational, prospective cohort study performed in nine ICUs from seven countries. Consecutive ICU patients with a Richmond Agitation-Sedation Scale (RASS) of −3 to 0 at the time of delirium assessment where a RASS ≤ 0 was secondary to a sedating medication. Patients were assessed with either the CAM-ICU or the ICDSC. Logistic regression analysis was used to account for factors with the potential to influence level of sedation or delirium occurrence. Results: Among 1660 patients, 1203 patients underwent 5741 CAM-ICU assessments [9.6% were delirium positive; at RASS = 0 (3.3% were delirium positive), RASS = −1 (19.3%), RASS = −2 (35.1%); RASS = −3 (39.0%)]. The other 457 patients underwent 3210 ICDSC assessments [11.6% delirium positive; at RASS = 0 (4.9% were delirium positive), RASS = −1 (15.8%), RASS = −2 (26.6%); RASS = −3 (20.6%)]. A RASS of −3 was associated with more positive delirium evaluations (odds ratio: 2.31; 95% confidence interval: 1.34–3.98) in the CAM-ICU–assessed patients (vs. the ICDSC-assessed patients). At a RASS of 0, assessment with the CAM-ICU (vs. the ICDSC) was associated with fewer positive delirium evaluations (odds ratio: 0.58; 95% confidence interval: 0.43–0.78). At a RASS of −1 or −2, no association was found between the delirium assessment method used (i.e., CAM-ICU or ICDSC) and a positive delirium evaluation. Conclusions: The influence of level of sedation on a delirium assessment result depends on whether the CAM-ICU or ICDSC is used. Bedside ICU nurses should consider these results when evaluating their sedated patients for delirium. Future research is necessary to compare the CAM-ICU and the ICDSC simultaneously in sedated and nonsedated ICU patients. Trial registration: ClinicalTrials.gov ; NCT02518646